Sosialisasi dan Simulasi Tanggap Bencana Gunung Meletus dan Banjir Desa Sumberagung Kecamatan Gandusari - Palupi Puspitorini; Yely Sulistyawati (Abdimas Universal, 2020)
Geographically, Sumberagung Village is located near an active volcano, Kelud Mountain. With such geographical conditions, it is very possible that natural disasters occur, ranging from volcanic natural disasters and cold lava floods in the Kali Putih River Region. With the frequent occurrence of disasters it is necessary to increase the readiness in dealing with disasters in the Sumberagung Village community, it is very necessary to conduct socialization to provide insight and knowledge to the community. The method used is to conduct direct socialization in the field, giving questionnaires, and coupled with literature studies from various sources, to conduct socialization to elementary / MI students in Sumberagung Village, Gandusari District, Blitar Regency. To improve disaster response and be smart in absorbing information on elementary / MI children as an early step, it is very necessary to socialize and simulate the SD / MI children in Sumberagung Village. The entire community and SD / MI students in Sumberagung Village have a very good response to the socialization activities and disaster response simulations that have been carried out, so that they are ready to assist and support the installation of placards for evacuation routes in Sumberagung Village, Gandusari District, Blitar Regency.